Analisis efektivitas biaya dan profil penurunan kadar glukosa darah penggunaan metformin dan glimepirid pasien diabetes melitus tipe 2 di RSUD R. Syamsudin, SH. - Honifa, Honifa; Rokhmah , Nisa Najwa; Zunnita, Oktaviana; Elina, Elina (Journal of Pharmaceutical and Sciences, 2025)
Hyperglycemia caused by abnormalities in insulin secretion and insulin function is a hallmark of a metabolic disorder known as diabetes mellitus (DM). The choice of alternative medications for DM varies significantly, making it essential to consider cost to ensure that the selected drug remains affordable while providing the best therapeutic effect. The purpose of this study is to examine the glucose-lowering profile and identify the most cost-effective antidiabetic drug for use in type 2 diabetes patients in the outpatient unit at RSUD R. Syamsudin, SH. Kota Sukabumi. This non-experimental study uses a descriptive design by reviewing the medical records of outpatients from the pharmacy department. Random blood glucose levels and medication costs are the parameters used. The results of the study showed that the use of the antidiabetic drug glimepiride, which is the most cost-effective drug for type 2 diabetes mellitus patients, demonstrated an average blood glucose reduction of 26.92% for patients using metformin and 22.97% for patients using glimepiride.